Implementation of Guided Inquiry Model in Human Movement System Learning to Improve Students' Science Literacy Skills - Agustina, Rezeki Sri (Gunung Djati Conference Series, 2025)
This study aims to determine the effect of the application of a guided inquiry model on the scientific literacy skills of grade XI high school students. The study was conducted at SMA Negeri 1 Aek Natas with a sample of 2 classes determined by cluster random sampling technique, namely the experimental class of 35 students and the control class of 34 students. Research data were collected using a test instrument consisting of a scientific literacy ability test (5 essay questions). Data were analyzed using an independent sample t-test approach with the help of the SPSS program. The results of the study showed that: the application of a guided inquiry model assisted by the Kodular application had an effect on students' scientific literacy skills (p = 0.013).